Agile Leadership – An Online-Based Advanced Training Programme for Leaders Including Personal (online) Coaching Sessions - Fielitz, Anja; Hug, Carolin (International Journal of Advanced Corporate Learning (iJAC), 2019)
Leadership today is characterised by rapid changes, increased complexity, unpredictability and contrariness. Personnel management requires flexibility and empathy, allowing leaders to respond to employees on an individual basis, to inspire and motivate them and to promote their entrepreneurial spirit. Agility is the key concept for this purpose.